THE STRUCTURE AND STRATEGY OF LOCAL STRONGMEN IN THE DEFEAT OF INDEPENDENT CANDIDATES: A QUALITATIVE STUDY - Lubis; Setiyono, Budi; Kushandajani; Sardini, Nur Hidayat (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The phenomenon of local strongmen is an integral part of understanding the dynamics of power and politics in peripheral regions such as Sumbawa, West Nusa Tenggara. Although the direct regional head election system has opened up broader opportunities for political participation, the dominance of local power often constrains the emergence of democratic alternatives. Independent candidates face various administrative and financial obstacles, as well as political pressure from deeply rooted local power networks. This study aims to examine the power strategies employed by Zulkieflimansyah, a prominent local figure in Sumbawa, in strategically utilizing formal and informal power to defeat independent candidates. This study used a qualitative case study approach with data collected through in-depth interviews with eleven purposively selected informants, including political actors, community leaders, and campaign team members.  The findings show that the influence of local strongmen extends across various sectors, including politics, education, local government, and customary systems. This influence is exercised through control over strategic resources, dominance of formal authority, and the systematic expansion of social and economic networks that enable long-term consolidation of power and suppression of political alternatives. The study finds that strategic political positions and strong social ties are key factors in delegitimizing and defeating independent candidates. These strategies strengthen local strongmen’s dominance within vertical and horizontal power structures, limiting fair political competition. Regulatory reform, resource transparency, and civic political education are needed to counter this dominance.JEL Classification Codes: D72.